IMPLIKASI PROJECT BASED LEARNING (PjBL) TERHADAP PENINGKATAN KEMANDIRIAN DAN MOTIVASI BELAJAR SISWA DI KELAS XI SMK NEGERI 4 MEDAN - Margaretha Hutabarat; Elisabeth Margareta; Sanggam Pardede (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the implications of the Project-Based Learning (PjBL) model on students’ independence and learning motivation in class XI at SMK Negeri 4 Medan. The research employed a quantitative explanatory approach with a sample of 56 students selected through purposive sampling. Data were collected using validated and reliable questionnaires supported by observation. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The results showed that the implementation of PjBL had a significant effect on students’ independence and learning motivation, as indicated by t-count greater than t-table (7.677 > 2.052) and a significance value of 0.000 < 0.05. These findings indicate that PjBL enhances student engagement, encourages responsibility in learning, and improves learning motivation. Therefore, it can be concluded that the Project-Based Learning model has a significant positive implication in improving students’ independence and learning motivation